Research on the Optimization of Marketing Strategy of Tea Enterprises in Zunyi, Guizhou Province - Jin, Feng; Apibunyopas, Jeerakiat (Science, Technology, and Social Sciences Procedia, 2023)
China is the birthplace of green tea, and also the world’s largest consumer and producer of tea, and Guizhou Province plays an important role in China’s tea industry. Even in the face of the Covid-19 pandemic and the adverse impact of the macroeconomic situation, Guizhou tea industry still showed a strong momentum of development in 2020. This paper focuses on the optimization of marketing strategy of tea enterprises in the development of Guizhou tea industry. The following research questions are put forward: What are the demographic characteristics of tea consumers in Zunyi, Guizhou Province; what are the attitudes and preferences of tea consumers in Zunyi, Guizhou Province; how satisfied are tea consumers in Zunyi, Guizhou Province with the quality, price, and variety of tea products; what are the potential opportunities and strategies for tea enterprises in Zunyi, Guizhou Province to improve their marketing and expand their market share? From the collection and analysis of questionnaires, there are differences between men and women in Zunyi city Guizhou province who have both online consumption experience and offline consumption experience. Male consumers of tea are much more than female consumers. The ages of tea consumers are between 26 - 45 and 46 - 55 years. Education distribution accounts for more than two-thirds of those who have received a bachelor’s degree or above. For the middle- and high-income groups with a monthly income of 4,001 - 8,000 yuan and 8,001 - 12,000 yuan, is the main consumer group of tea purchase. The data analysis results of are generally unsatisfactory, among which product promotion activities, tasting activities, product information access channels, and the linkage between online and offline channels have the lowest average professional satisfaction of sales staff. Women are less satisfied with pricing strategies and channel strategies, and have a large gap with men.